(3JYdjbI aj GddaXs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3hddeObb GdTjQhGfj aj JYdjbI GdeYGde YHGQI aj HMK GdGTJQGc aj QO eG GNJGQg GdeGJfs
(3BNQgG (B:s
(3BNQgG(B: (3adG jLH JLQjO aj eYfi GddaX YfO EQGOI VO GdhMOI, abhdg(B: (3gPG efY deG jJaQY Ydi OYhi GdeGJf ef JHGOQ EQGOI GdhMOI HGdhLg GdKGef HefY Jdc GdOYhis
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GddZIs